(untitled) (International Journal of Engineering and Computer Science, 2017)
Question-Answering(QA) is a new research area/ region in the field of Information science which comes into focus in last few decade. The present study is undertaken to survey about the QA system.The study in this paper will provide the guidelines to the researchers, scholars and practitioners of computer engineering. In this paper, the study is undertaken by planning, conducting, evaluating and reporting the literature review from the past years. A Question –Answering system consists of three core components i.e. question classification ,information retrieval and answer extraction module. This paper aims at giving an overview in this field, evaluating the current and emerging status and visualizing the future scope and trends.